Survey of Perceptions of Health Care Professionals in the United Kingdom toward Uterine Transplant. (March 2015) - Saso, Srdjan; Clarke, Alex; Bracewell-Milnes, Timothy; Al-Memar, Maya; Hamed, Ali Hassan; Thum, Meen-Yau; Ghaem-Maghami, Sadaf; Del Priore, Giuseppe; Smith, J. Richard
Context: Currently, the only 2 options that women with absolute uterine factor infertility have for managing their infertility are surragocy or adoption. These women may also benefit from a possible future third option: uterine transplant Objective: To investigate the opinions and views of UK health care professionals toward uterine transplant and rank issues related to uterine transplant by importance in order to make uterine transplant transparent and understandable to colleagues. Design: Large, in-depth survey investigating health care professionals' opinions on uterine transplant. Setting: Analysis done at Imperial College London. Participants: UK transplant professionals (surgeons, nurses, operating room staff, and donor coordinators) and obstetricians and gynecologists (trainees, members, and fellows of the Royal College of Obstetricians and Gynaecologists). Intervention: Questionnaires were given out at hospital grand rounds, trainee teaching days, and conferences (national and international). Main Outcome Measures: Should uterine transplant take place? Is uterine transplant achievable? What is the rank order of importance of key issues related to uterine transplant? Results: The study had 528 participants. With respect to overall support for uterine transplant and as a possible future therapeutic option for absolute uterine factor infertility, 93.8% (n=495) thought that uterine transplant should take place if considered appropriate medically, surgically, and ethically and 57.2% (n= 302) thought it was an achievable objective. Issues related to immunology of uterine transplant and pregnancy after uterine transplant were unanimously thought of as most important. More effort is required to educate health care professionals about all aspects of uterine transplant.